Classification and definition of epilepsy. Position paper by the International League Against Epilepsy on Nosology and Definitions of Epilepsy Syndromes dated 2021 - K. Yu. Mukhin; O. A. Pylaeva; V. S. Kakaulina; M. Yu. Bobylova (Русский журнал детской неврологии)
This article presents updated and revised diagnostic criteria for epilepsy syndromes proposed in 2021 by the Nosology and Definitions Taskforce of the International League Against Epilepsy (ILAE). The current classification of epilepsy syndromes was developed in 1989. The new ILAE Classification and Definition of Epilepsy Syndromes is a result of huge work of many experts from all over the world. The draft of the new classification is presented on the ILAE website for wide discussion. It includes 4 main sections: 1) classification and definition of epilepsy syndrome with onset in neonates and infants; 2) classification and definition of epilepsy syndromes with onset in childhood; 3) classification and definition of epilepsy syndromes with onset at a variable age; 4) definition of the idiopathic generalized epilepsy syndromes. Each section is based on a thorough analysis of literature and clinical experience of experts. Its main purpose is to identify epilepsy syndromes using the 2017 ILAE classification of epilepsy forms and types of epileptic seizures, as well as to identify specific characteristics of each syndrome to improve clinical diagnosis. For each syndrome, the document provides the details on its epidemiology, clinical manifestations, types of seizures, electroencephalographic features, neuroimaging signs, genetic examination, as well as differential diagnosis with other epilepsy syndromes and various non-epileptic conditions. It introduces mandatory criteria that must be present in order to diagnose the syndrome and alert criteria that are absent in the vast majority of cases within a syndrome, but rarely can be seen. Particular attention is paid to exclusionary criteria that must be absent in order to diagnose the syndrome. When developing the criteria for each epilepsy syndrome, the ILAE Task Force used the latest literature data, including Internet resources and the opinion of experts in this area. The international classification should be applied by specialists from all over the world. It should contain clear and easy-to-understand definitions; the language should be simple and understandable. The new ILAE classification demonstrates revised definitions of well-known electroclinical epilepsy syndromes and proposes a new concept of defining epilepsy syndromes by their etiology (including those syndromes in which pathogenic mutations or structural changes correlate significantly with certain electroclinical phenotype). It also introduces a new etiology-defined class of epilepsy syndromes characterized by specific genetic, metabolic, and structural causes. The document does not cover therapy for epilepsy syndromes; however, for some of them, it specifies the most effective or potentially aggravating antiepileptic drugs. The prospect of further targeted gene therapies development and approval of antiepileptic drugs specific for certain epilepsy syndromes after randomized clinical trials had served as a powerful motivation to introduce the concept of epilepsy syndromes determined primarily by etiology. In conclusion, the authors discuss the Classification and Definition of Epilepsy Syndromes, propose their ideas, comments, suggestions, and observations. This article aims to familiarize a wide range of specialists with the new ILAE classification and its details. In addition to a detailed description of the abovementioned document, the article provides information on the currently existing classification principles for epilepsy and epileptic seizures. There is also a discussion with the authors’ comments on the ILAE Classification and Definition of Epilepsy Syndromes.